An impact of Extension Advisory Services on farmer: review - Kumar, Amit (International Journal of Social Science, 2024)
The study focused primarily on how extension services helped communities during the pandemic and discussed the implications of the research for the future work of extension services and its impact on agricultural production. About 80-85% of the farmers are working with a great risk of dry season. In contrast, extension projects that promote rural adult learning and agriculture-dependent economies have been essential vehicles for disseminating knowledge about agricultural technologies, helping farmers hone their managerial and technical skills. Extension programs are expected to decrease food insecurity and poverty and increase farm income. Extension advisory services address the knowledge gaps of agricultural workers working under difficult conditions. Restrictions on the movement of crowds have caused an unprecedented shift in daily life to a remote and virtual environment. Agents struggled to adapt their distribution model while delivering fast service to their customers in this unfamiliar environment. The work is based on material from case-specific project assessments, participant observations, organizational reports, documents analysis and actual interviews.